Pengembangan Buku Pembelajaran Pendidikan Jasmani Bagi Anak Usia Dini - Surahman, Fadli; Sanusi, Rahmat; Maulina Dewi, Tisrin (UIR Press, 2020)
The problem in this research is the availability of textbook teaching physical education for early childhood or manual for sports teachers in schools is still there, in the previous learning still uses the book physical education in general. The aim of this research is generating a guide text book for teacher at PAUD and Kindergarten in physical education and recreation learning. This study is the research of development that refers from Borg and Gall concept which is shortened to seven steps as needed. Small-scale testing involves 10 subjects and field testing involves 35 subjects. In order the resulting product can be valid so in this study involves three validators consisting of motor experts, physical education learning experts and early childhood education learning experts. From the result of small-scale trials of expert validation is obtained an average score of 3.5 with the category of